2017
DOI: 10.1017/s0959270916000484
|View full text |Cite
|
Sign up to set email alerts
|

On the brink: status and breeding ecology of Eleonora’s FalconFalco eleonoraein Algeria

Abstract: SummaryThis is the first study reporting the population status and reproductive biology of the Eleonora’s Falcon in Algeria. To determine the status, nest site selection, and breeding parameters, data were collected at Chetaïbi, north-east Algeria in 2010 and 2012. During this period, the number of breeding pairs decreased from 130 to 100, which represents an annual decrease rate of 12.29%. The mean clutch size was 2.6 ± 0.5 (n = 90) and 2.9 ± 0.4 (n = 34) in 2010 and 2012, respectively. Clutches displayed a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…Physical nest characteristics had limited effect on breeding success. The positive effect of deeper caves in contrast to the negative effect of smaller, shallower holes, on fledglings per successful pair, indicates that more exposed nests had fewer fledglings, in agreement with studies in other areas (Touati et al 2017), but our results are from a small sample of nests in caves and holes. The Episkopi colony had fewer fledglings per successful pair, something that needs further investigation possibly in relation to disturbance from human activities which are more intense compared to the other two colonies which are more isolated.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Physical nest characteristics had limited effect on breeding success. The positive effect of deeper caves in contrast to the negative effect of smaller, shallower holes, on fledglings per successful pair, indicates that more exposed nests had fewer fledglings, in agreement with studies in other areas (Touati et al 2017), but our results are from a small sample of nests in caves and holes. The Episkopi colony had fewer fledglings per successful pair, something that needs further investigation possibly in relation to disturbance from human activities which are more intense compared to the other two colonies which are more isolated.…”
Section: Discussionsupporting
confidence: 92%
“…CC-BY-NC-ND 4.0 International license made available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity. It is The copyright holder for this preprint this version posted May 15, 2020. ; https://doi.org/10.1101/2020.05.04.077248 doi: bioRxiv preprint 5 Eleonora's falcon (Falco eleonorae Géné, 1839) is a social raptor with a total population of ~15,000 breeding pairs (Walter 1979;BirdLife International 2017;Touati et al 2017), breeding primarily on islands and islets in the Aegean Sea (Dimalexis et al 2008). The breeding population though ranges from Cyprus in the east, westwards across the Mediterranean Sea, the Atlantic coast of Morocco and the Canary Islands (Walter 1979).…”
Section: Study Speciesmentioning
confidence: 99%
“…1–3 Besides, several Algerian wetlands are of crucial importance for the conservation and reproduction of several rare, endangered or restricted-range avian species such as the Audouin’s Gull ( Larus audouinii ), White-headed Duck ( Oxyura leucocephala ), Ferruginous Duck ( Aythya nyroca ), Marbled Teal ( Marmaronetta angustirostris ) 3,4 and Eleonora’s Falcon ( Falco eleonorae ). 5,6 Despite their multiple ecological services and values, only few studies have demonstrated the ecological role of North African wetlands in the maintenance of migratory waterbirds. 7–15 Nevertheless, and with all the studies cited above, the subject is far from being fully addressed, in particular when considering climate change and drought effects that are escalating on all North African ecosystems, including wetlands.…”
Section: Introductionmentioning
confidence: 99%
“…Unpublished data (F. Samraoui, unpub.) allowed us to assess changes in the wintering peak population in the period 2015-2018 by calculating the annual growth rate using the formula ((f/s)^(1/t)-1)*100, where f and s are the final and starting values, respectively, and t represents the elapsed period between the two (Touati et al 2017). Likewise, the data for the breeding season of 2008 (Samraoui et al 2013) allowed us to estimate changes in the number of active nests in the period 2008-2018 using the same formula.…”
Section: Land Cover Change and Population Monitoringmentioning
confidence: 99%